Antecedents of consumers’ green product purchase intention: an insight from Ethiopia - Yebcha Fenta; Manjit Singh; Raj Kumar Gautam (Cogent Business & Management, 2024)
Globally, companies and individuals are increasingly concerned with green practices as essential in developing competitive advantages. Companies must manage their environmental practices to survive today’s competitive, dynamic, and turbulent environment. Considering these concerns, this study explores factors that affect consumers’ green purchase intentions (GPI). The study model was validated theoretically and empirically using surveys. The questionnaire was administered to 358 young consumers using convenience sampling. Smart PLS-Structural equation modelling (SEM) was used to evaluate the model. The findings show that attitude, subjective norms, and perceived behavioural control had a direct and environmental knowledge indirectly impacted the intention to make green purchases. The study provided vital insights into academic and practical viewpoints and society’s need to maintain, protect, and survive in the face of environmental challenges.The study shows that people in Ethiopia still have low levels of knowledge about the benefits of eco-friendly products. Therefore, it is incumbent upon practitioners and policymakers to make an effort to educate people on the same.